The Applicable Law on Cross-Border Flexible Employment Contracts According to Jordanian Legislation - Alnatshah, Abed Aljawad Daoud (Dirasat: Shari'a and Law Sciences, 2025)
Objectives: To develop a legal framework that defines how cross-border flexible work contracts, often concluded electronically between parties with a foreign element, operate. This includes their scope, conditions, and legal implications, particularly focusing on the applicable law, whether at the domestic or international level. Methods: The descriptive-analytical approach was used, examining and analyzing the legal texts regulating flexible work contracts in Jordanian legislation, such as the Labor Law and the Flexible Work System, along with the conflict of laws rules in the Civil Code related to contractual relationships. Results: The legislator included conflict-of-laws rules in Article 20 of the Jordanian Civil Code, applying these rules sequentially rather than by choice, meaning the primary connecting factor must be used first. If not available, the next in sequence must be applied. This necessitates investigating the possibility of adopting the will theory outlined in Article 20 of the Jordanian Civil Code and applying it to cross-border flexible work contracts concluded remotely. Conclusion: It is possible to adopt the agreement made between the parties of the flexible work contract and apply the foreign law agreed upon between the parties, but only if that law offers better rights to the worker than those provided by Jordanian labor law. This aligns with the theory of the better-rights principle in labor contracts, as outlined in Article 4(a) of the Labor Law.